2019
DOI: 10.1124/jpet.118.254375
|View full text |Cite
|
Sign up to set email alerts
|

Differential Free Intracellular Calcium Release by Class II Antiarrhythmics in Cancer Cell Lines

Abstract: Class II antiarrhythmics or b-blockers are antisympathetic nervous system agents that act by blocking b-adrenoceptors. Despite their common clinical use, little is known about the effects of b-blockers on free intracellular calcium (Ca 21 i), an important cytosolic second messenger and a key regulator of cell function. We investigated the role of four chemical analogs, commonly prescribed b-blockers (atenolol, metoprolol, propranolol, and sotalol), on Ca 21 i release and whole-cell currents in mammalian cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 92 publications
(128 reference statements)
0
6
0
Order By: Relevance
“…26 Propranolol induces apoptosis in CM cell lines 19 through non-selective β1 and β2-AR antagonism that may inhibit ERK/MAPK1/3 as well as negatively block the ERK/MAPK pathway by releasing intracellular calcium. 27 Increased intracellular Ca 2+ in CM can induce the WNT signaling cascade, responsible for activating PKC and CamKII. 28 In UM, among the downstream effectors of GNAQ/11, the main function of the second messenger IP3 is to activate PKC by increasing the cytosol calcium levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Propranolol induces apoptosis in CM cell lines 19 through non-selective β1 and β2-AR antagonism that may inhibit ERK/MAPK1/3 as well as negatively block the ERK/MAPK pathway by releasing intracellular calcium. 27 Increased intracellular Ca 2+ in CM can induce the WNT signaling cascade, responsible for activating PKC and CamKII. 28 In UM, among the downstream effectors of GNAQ/11, the main function of the second messenger IP3 is to activate PKC by increasing the cytosol calcium levels.…”
Section: Discussionmentioning
confidence: 99%
“…β‐AR 1, 2, and 3 can activate ERK/MAPK1/3 . Propranolol induces apoptosis in CM cell lines through non‐selective β1 and β2‐AR antagonism that may inhibit ERK/MAPK1/3 as well as negatively block the ERK/MAPK pathway by releasing intracellular calcium . Increased intracellular Ca 2+ in CM can induce the WNT signaling cascade, responsible for activating PKC and CamKII .…”
Section: Discussionmentioning
confidence: 99%
“…Among all the organelles, the endoplasmic reticulum has been shown to be the main Ca 2þ store in most cell types. 30 Thus, the role of the endoplasmic reticulum in bifenthrin-evoked Ca 2þ release in PC3 cells was explored. The BHQ-sensitive endoplasmic reticulum store appears to be the pivotal Ca 2þ store.…”
Section: Discussionmentioning
confidence: 99%
“…Liver inflammation, pleural effusion and bone marrow depression have also been reported as critical adverse effects associated with prolonged use of DTN 1,9 . Long‐term use of a low dose of DTN (<400 mg/day) is relatively safe and not associated with the development of liver injury 10 . Chen et al 11 reported that venous thromboembolism may develop following a large dose of DTN therapy (>400 mg/day) for malignant hyperthermia.…”
Section: Introductionmentioning
confidence: 99%
“…1,9 Longterm use of a low dose of DTN (<400 mg/day) is relatively safe and not associated with the development of liver injury. 10 Chen et al 11 reported that venous thromboembolism may develop following a large dose of DTN therapy (>400 mg/day) for malignant hyperthermia. The underlying cause of thromboembolism in DTN therapy is because of muscle weakness-induced thrombogenesis.…”
mentioning
confidence: 99%